Comparative Study of the Geopolymers Synthesized from Various Types of Construction Wastes - Pathak, Arvind; Jha, Vinay Kumar (Nepal Journal of Science and Technology, 2013)
Demolition of old houses and construction of new buildings are in peak in urban sectors which generate a huge amount of construction wastes. These wastes are rich source of alumino-silicate. Geopolymerization can transform a wide range of alumino-silicate materials into building materials with excellent physicochemical properties. Thus, geopolymers have been synthesized from construction wastes such as sand-cement-mixture (SCM), concrete mixture (CM), brick dust (BD), etc using alkali and alkali-silicate as activators. Parameters like alkali concentration (for dissolution of alumino-silicate), ratio of alkali-silicate to construction wastes and curing time were varied to improve the quality of geopolymeric products. The maximum compressive strengths of geopolymeric products obtained from BD, SCM and CM were 60.0, 47.0 and 45.5 MPa respectively. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 81-86 DOI: http://dx.doi.org/10.3126/njst.v14i1.8926